Analysis of Capital, Labor, Education Level, and Access to Finance on UMKM Turnover Growth in Plaju Darat - Tobing, Batara Reinhard Partogi L; Ramadhan, Anggia; Fadlan, Ahmad (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effects of business capital, labour size, the educational attainment of entrepreneurs, and access to finance on the growth of UMKM turnover in Plaju Darat Subdistrict, Palembang City. The study adopts a quantitative approach using secondary data for the period 2013-2024 obtained from Statistics Indonesia and the Palembang City Office of Cooperatives and UMKM. Multiple linear regression is employed as the analytical method. The findings indicate that business capital and labour size have a positive and statistically significant effect on UMKM turnover growth, while the educational attainment of entrepreneurs has no significant effect. Meanwhile, access to finance has a negative and statistically significant effect, indicating that the short-term burden of formal financing constrains UMKM turnover performance. Simultaneously, all four independent variables significantly affect UMKM turnover growth, with the model demonstrating a very high level of explanatory power. These results underscore the importance of strengthening internal production factors and adopting more adaptive financing policies to promote sustainable UMKM growth.